Business authority in global governance: Beyond public and private - Janne Mende (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
This paper discusses the concept of authority in global governance by unpacking the components that characterize its various notions. These components are the triadic relationship between power, legitimacy, and the reference to public interests, and how they are embedded in the constellation between public and private. After clarifying each of these components, the article applies them to business enterprises - key actors in global governance -, focusing on the issue area of business and human rights. The paper shows that business authority does not neatly fit into the public-private distinction that is pervasive in conceptions of global governance and the international human rights regime. Instead, businesses have public and private, as well as hybrid, roles in global governance. Business authority then forms a peculiar third, next to public authority and private authority. Accordingly, the paper suggests extending the two-pole constellation of public and private into a three-pole constellation, with business building a peculiar third position between and beyond the public and the private. This approach allows furthering the understanding of business authority in global governance in particular and the concept of authority in global governance more generally. – – Den pluralen Perspektiven auf Autorität in der Global Governance sind vier Elemente gemeinsam. Autorität lässt sich demnach bestimmen als ein triadisches Verhältnis zwischen Macht, Legitimität und dem Bezug auf öffentliche Interessen. Diese Triade ist eingebettet in eine vermittelte Konstellation von Öffentlichkeit und Privatheit. Nach einer konzeptuellen Klärung dieser vier Elemente von Autorität diskutiert das Paper Unternehmen als zentrale Governance-Akteure im Themenbereich Wirtschaft und Menschenrechte. Deutlich wird, dass die Autorität von Unternehmen sich nicht in die Unterscheidung von öffentlich und privat einordnen lässt, die gleichwohl für die Governance-Forschung und für das internationale Menschenrechtsregime prägend ist. Vielmehr haben Unternehmen sowohl öffentliche als auch private und darüber hinaus auch hybride Governance-Rollen inne. Ausgehend von den Konzepten privater Autorität und öffentlicher Autorität schlägt das Paper daher vor, Unternehmens-Autorität als eine dritte Form zu verstehen, die gleichzeitig zwischen und jenseits von Öffentlichkeit und Privatheit situiert ist. Diese Perspektive trägt zu einem erweiterten Verständnis von Unternehmens-Autorität in der Global Governance bei und erlaubt sowohl konzeptuelle als auch normative Anknüpfungspunkte.
Keywords: 320; Authority; power; legitimacy; global governance; human rights; business enterprises; public interests; Autorität; Macht; Legitimität; Global Governance; Menschenrechte; Unternehmen; öffentliche Interessen